Vulnerability of clustered makeshift houses to severe wind loadings - Diño, Joseph Romeo M. (College of Engineering, University of the Philippines Diliman, 2013)
Makeshift structures, houses that are typically seen in slums, are very common in the Philippines nowadays. This study aims to focus on the said structures by assessing their susceptibility to damage when subjected to severe wind loads through the generation of fragility and vulnerability curves. The paper discusses an approach for developing the said curves by modeling isolated and clustered housing cases of makeshift houses using finite element method and computational fluid dynamics under severe winds. A survey on various localities in Metro Manila was conducted to determine the typical makeshift structure which is modeled in the software ANSYS. A typhoon simulation was done subjecting the model to increasing wind speeds, varying the wind's direction. The damage states were then identified for every wind speed and direction, applying the HAZUS-MH Damage-state Definition developed by Vickery et al in 2006. This became the basis of the fragility curve development. Cost estimates of typical makeshift houses were also accomplished to determine the damage index in terms of costs which will be the tool to plot the vulnerability curve. Results show that the isolated houses, although rarely the case, is much susceptible to typhoons. In the clustered houses, the houses around the perimeter contribute to the immediate takeoff at an early wind speed of 65 kph, while the house at the center experiences the damage at 90 kph demonstrating the positive effects of shielding. The results also incorporated the data from actual typhoons collected by P AGASA which indicated complete damage of houses at a lower wind speed than the analytical results. This may indicate possible significant effects of damages due to debris